2023
DOI: 10.1097/bpo.0000000000002347
|View full text |Cite
|
Sign up to set email alerts
|

Does Transitioning to a Brace Improve HRQoL After Casting for Early Onset Scoliosis?

Abstract: Background: Serial casting is favored for the initial treatment of early onset scoliosis (EOS), but there is concern about significant morbidity and caregiver burden. Studies have examined the utility of bracing as an alternative to casting, but little is known about differences in health-related quality of life (HRQoL) between treatments. We hypothesized that patients with a diagnosis of idiopathic EOS experience an improvement in HRQoL when transitioning from serial casting to bracing as measured by the 24-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…They also found improvement in the quality of life of the patients and their families as measured by the EOSQ-24. Henstenburg et al [18], however, found in their study that patients treated with casting for EOS experience reversible declines in HRQoL. After patients transition from casting to bracing, EOSQ scores recovered to pretreatment baseline levels and were maintained at last followup [18], which suggests better tolerance of bracing over casting.…”
Section: Castingmentioning
confidence: 90%
“…They also found improvement in the quality of life of the patients and their families as measured by the EOSQ-24. Henstenburg et al [18], however, found in their study that patients treated with casting for EOS experience reversible declines in HRQoL. After patients transition from casting to bracing, EOSQ scores recovered to pretreatment baseline levels and were maintained at last followup [18], which suggests better tolerance of bracing over casting.…”
Section: Castingmentioning
confidence: 90%